Polarimetric Radar for Automotive Applications - Visentin, Tristan (Karlsruher Forschungsberichte aus dem Institut für Hochfrequenztechnik und Elektronik, 2019)
Current automotive radar sensors prove to be a weather robust and low-cost solution, but are suffering from low resolution and are not capable of classifying detected targets. However, for future applications like autonomous driving, such features are becoming ever increasingly important. On the basis of successful state-of-the-art applications, this work presents the first in-depth analysis and ground-breaking, novel results of polarimetric millimeter wave radars for automotive applications.